Existential Risks to Humanity Should Concern International Policymakers and More Could Be Done in Considering Them at the International Governance Level. Issue 11 (20th July 2020) - Boyd, Matt; Wilson, Nick
Abstract: In this perspective, we consider the possible role of the United Nations (UN) with respect to existential risks to human civilization and the survival of humanity. We illustrate how existential risks have been discussed at an international governance level, specifically in documents in the UN Digital Library. In this large corpus, discussions of nuclear war account for over two‐thirds (69%, 67/97) of mentions of existential risks, while mention of other existential risks, or such risks as a category, appears scant. We take these observations to imply inadequate attention to these significant threats. These deficits, combined with the need for a global response to many risks, suggest that UN member nations should urgently advocate for appropriate action at the UN to address threats, such as artificial intelligence, synthetic biology, geoengineering, and supervolcanic eruption, in analogous fashion to existing attempts to mitigate the threats from nuclear war or near‐Earth objects.